PENGARUH METODE PEMBELAJARAN SNOWBALL THROWING BERBANTUAN MEDIA GAMBAR TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS V SD NEGERI 22 SALONGGE KABUPATEN ENREKANG - Maria Sulfa; Aliem Bahri; Sri Rahayu (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
This type of research is pre-experimental research in the form of Pre Test Post Test Design, namely an experiment which in its implementation only involves one class as an experimental class without a comparison class (control class) which aims to determine the influence of the Snowball Throwing Learning Model Assisted with Image Media on the Ability to Write Text. Explanation of Class V Students of SD Negeri 22 Salongge, Enrekang Regency. 2023/2024 academic year. The experimental units in this research were 15 Class V students. The research was carried out over 4 meetings. The success of the learning process is viewed from aspects, namely: achievement of complete learning outcomes in writing explanatory text, student activities in learning to write explanatory text. Learning is said to be successful if the above aspects are met. The data collection technique used was writing score data collected using a writing test, data about student activities in learning to write an explanatory test was collected using an observation sheet on student learning activities. The results of descriptive statistical analysis of the use of the Snowball Throwing Learning Model on explanatory text writing skills, explanatory text writing skills assisted by image media using the Snowball Throwing learning method show better learning results than before the Snowball Throwing learning model was applied. The results of inferential statistical analysis using the t test formula, it is known that the calculated t value obtained is 7.89 with frequency (db) = 15–1 = 14, at a significance level of 5% obtained t table = 2.145. So, t count > t table or the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is an influence in applying the Snowball Throwing learning method assisted by image media on the ability to write explanatory text in class V students at SD Negeri 22 Salongge, Enrekang district.